Cover Image, Volume 132, Issue 21. Issue 21 (5th June 2015) - Escobar, Isabel C.; Van der Bruggen, Bart
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Hollow fiber membranes are used in hemodialysis to clear the blood of uremic toxins. During hemodialysis, lipopolysaccharides (LPS) in contaminated dialysate solution may translocate across the hollow fiber membrane to a patient's blood, resulting in fever and possible systemic shock. Ben Madsen, David W. Britt, Chih‐Hu Ho, Michael Henrie, Cheryl Ford, Eric Stroup, Brent Maltby, Doug Olmstead and Marion Andersen explore how different chemical and structural modifications to polysulfone/polyvinyl pyrrolidone hollow fiber membranes influence LPS distribution. The cover shows a native Fresenius Optiflux® F200NRe membrane (center) and clockwise, from top left, bleach‐treated, PS‐PEG copolymer, low‐PVP, and high‐PVP membranes. DOI: 10.1002/app.41550